Using Complex Networks to Assess Collaboration in Rap Music - A Study Case of DJ Khaled - Araújo, Carlos V. S.; M. Neto, Rayol; Nakamura, Fabíola G.; Nakamura, Eduardo F (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
DJ Khaled is a popular musician that is known for having many collaborators in his songs. Hence, in this paper, we model the evolution of DJ Khaled’s collaboration network as nine different networks that incrementally consider the albums of his discography. The network of each album includes the collaborations from previous ones and adds the collaborations from the new album. The artists are represented as nodes and the edges are the number of songs they appear together. Our focus is to answer whether or not: (i) we can identify meaningful communities in this network; and (2) there is an artist who has greater influence as networks emerges. By using the network average clustering coefficient, we found that the artists in the the network tend to naturally cluster in a logical manner. As a result, we identified nine communities, six of them are meaningful, and we identified the rapper Rick Ross as the most influential artist of the network.